Blockade of angiotensin AT1 receptors prevents arterial remodelling and stiffening in iron‐overloaded rats. (3rd January 2020) - Fidelis, Helbert Gabriel; Mageski, Jandinay Gonzaga Alexandre; Goes, Susana Curry Evangelista; Botelho, Tatiani; Marques, Vinicius Bermond; Ávila, Renata Andrade; dos Santos, Leonardo
Abstract : Background and Purpose: Damage to the vasculature caused by chronic iron‐overload in both humans and animal models, is characterized by endothelial dysfunction and reduced compliance. In vitro, blockade of the angiotensin II AT1 receptors reversed functional vascular changes induced by chronic iron‐overload. In this study, the effect of chronic AT1 receptor blockade on aorta stiffening was assessed in iron‐overloaded rats. Experimental Approach: Male Wistar rats were treated for 15 days with saline as control group, iron dextran 200 mg·kg −1 ·day −1, 5 days a week (iron‐overload group), losartan (20 mg·kg −1 ·day −1 in drinking water), and iron dextran plus losartan. Mechanical properties of the aorta were assessed in vivo. In vitro, aortic geometry and biochemical composition were assessed with morphometric and histological methods. Key Results: Thoracoabdominal aortic pulse wave velocity (PWV) increased significantly, indicating a decrease in aortic compliance. Co‐treatment with losartan prevented changes on PWV, β‐index, and elastic modulus in iron‐overloaded rats. This iron‐related increase in PWV was not related to changes in aortic geometry and wall stress. but to increased elastic modulus/wall stress ratio, suggesting that a change in the composition of the wall was responsible for the stiffness. Losartan treatment also ameliorated the increase in aorta collagen content of the iron‐overload group, without affecting circulating iron or vascular deposits. Conclusions and Implications: Losartan prevented the structural and functional indices of aortic stiffness in iron‐overloaded rats, implying that inhibition of the renin–angiotensin system would limit the vascular remodelling in chronic iron‐overload. Abstract :